Siluro-Devonian tectonostratigraphic relationships in the Portage Brook area, northern New Brunswick: implications for timing of deformational events in the Bathurst Mining Camp - Gower, S.; McCutcheon, S. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1997)
In the Portage Brook area, Siluro-Devonian rocks of the Chalcurs Bay Synclinorium are juxtaposed against polydeformcd Cambro-Ordovician rocks of the Bathurst Mining Camp along the northerly trending Portage Brook Fault. Rocks of the Chaleurs Group have been identified for the first time west of the Portage Brook Fault, and are subdivided into four lithological units: conglomerate, sandstone and siltstone of the Simpsons Field Formation; mafic volcanic rocks of the Bryant Point Formation; felsic volcanic rocks of the Benjamin Formation; and thickly bedded, brownish grey to reddish grey sandstone of the Greys Gulch Formation. The presence of two pre-deposi-tional cleavages in Ordovician pebbles in the middle Wcnlockian to late Ludlovian Simpsons Field Formation indicates that D2 deformation in the Bathurst Mining Camp started prior to the Late Silurian, i.e., earlier than considered by some workers. This observation is supported by the truncation of at least two strong fabrics in Cambro-Ordovician rocks by Late Silurian/Early Devonian mafic intrusions. An alkali granite (radiomctrically dated at 414 +11/-1 Ma) clearly intruded, and altered to hornfels, clastic rocks of the Simpsons Field Formation. The granite appears to grade laterally into and to be coeval with volcanic rocks of the Benjamin Formation, thus suggesting that the age of the intrusion is close to the lower error limit.